(untitled) (Central Medical College Journal, 2022)
Diabetic foot ulcer is a common cause of admission in the surgical wards and sometimes the first presentation of this debilitating disease. Numerous topical medication and gels are promoted for ulcer care and healing. Relatively few have proved to be more efficacious than normal saline dressing. This study aimed to compare the effect of topical insulin versus normal saline dressing in healing of diabetic foot ulcers at Rajshahi Medical College Hospital, Rajshahi. Aims and objectives: To assess the effect of topical insulin versus normal saline dressing in healing of diabetic foot ulcers. Methods: A total of 60 patients with diabetic foot ulcers were studied in different units of surgical ward of Rajshahi Medical College Hospital from July 2017 to June 2019. Patients were divided into two groups of 30 patients each that is group A (topical insulin) and group B (Normal saline). Ratio, mean, standard deviation, Pearson Chi-Square test were applied appropriately to this study. Results: Among the 60 patients, majority of the patients were males in both the groups (73.33% in group A and 80.00% in group B) with male to female ratio of 2.7:1 in group A and 4:1 in group B. The mean age in group A was 50.00±7.33 years and in group B it was 53.00±7.80 years, where P=1.00. Among patients with group A significant reduction of mean ulcer area was observed (314.30±171.26 mm2 ) with higher mean percentage reduction (15.30±3.28 percent), whereas, in group B the mean percentage reduction was significantly less (6.35±2.03 percent) with less reduction of mean final ulcer area (110.5±56.23mm2), where P<0.001. Conclusions: Topical insulin dressing provided better outcome in patients with diabetic foot ulcers by significant reduction in wound area when compared to normal saline dressing. Central Medical College Journal Vol 5 No 2 Jul 2021 PP 94-101